Relevansi Strategi Manajemen Risiko Pembiayaan dalam Konteks Perbankan Syariah - Rofiqoh Lubis, Nurul; Mutthaqin, Muhammad Satrya; Sugianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financing risk management in Islamic banking is a crucial aspect related to the identification, measurement, control and monitoring of risks that may arise in financing provided by Islamic financial institutions. challenges faced by sharia financial institutions in managing financing risks. One of them is risks related to financing that arise due to the complexity of transactions and fluctuating economic conditions. This research aims to analyze the types of sharia business risks, sharia business models, measurement processes and monitoring processes of financing risk management in sharia banking. The research method used in this study is qualitative research with a descriptive approach. A qualitative approach is used in this research because this study aims to describe and understand the complexity of financing risk management strategies in Islamic banking. The results of this research show that in sharia business risk management, there are several categories of business risk, including financing risk, market risk, liquidity risk and operational risk. Financing risk focuses on the customer's capability to repay the financing provided by sharia financial institutions. Sharia business models include a variety of business strategies rooted in Islamic sharia principles, such as fairness, honesty and impartiality. These sharia business models include manufacturing, distributors, retail, franchising, sharia banking, and sharia microfinance, each of which emphasizes products and services that comply with applicable sharia principles.